Physical Therapy Utilization Prior to Biceps Tenodesis or Tenotomy for Biceps Tendinopathy - Amy McDevitt; Joshua Cleland; Paisley Hiefield; Jonathan Bravman; Suzanne Snodgrass (North American Sports Medicine Institute, 2024)
# Introduction Surgery for the management of individuals with long head of the biceps tendon (LHBT) tendinopathy is common. Little is known about physical therapy (PT) utilization prior to surgery. The purpose of this review was to investigate the use of PT prior to biceps tenodesis and tenotomy surgeries by assessing the number of visits and the types of interventions. A secondary objective was to report on themes of PT interventions. # Methods A retrospective observational cohort study design was used to analyze medical records and report on patient visits, procedure codes based on active or passive interventions, and themes of interventions utilized by PT. # Results Patient records (n=308) were screened for eligibility, n=62 (20.1%) patients attended PT prior to surgery. The median number of PT visits was four (IQR=3.5), and 39/62 (63%) patients had four or more visits to PT. Active interventions were used in 54.5% (533/978) of the codes billed; passive interventions were used in 45.5% (445/978) of the codes. There was high utilization of therapeutic exercise \[93.4% (498/533) of active procedure codes\] including muscle performance/resistance, functional activity, motor control and stretching. Manual therapy \[84.3% (375/445) of passive procedure codes\] included soft tissue mobilization, non-thrust manipulation (glenohumeral joint and cervical spine) and thrust manipulation (thoracic spine). # Conclusions PT was not commonly utilized prior to undergoing biceps tenodesis and tenotomy surgery. Further research is needed to understand the reasons for low utilization. # Level of Evidence 3b